A MIXED DOPPLER SHIFT AND POLARIZATION MANAGEMENT APPROACH FOR SATELLITE COMMUNICATIONS (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2025)
The rapid displacement of satellites in low Earth orbit (LEO) poses several challenges for communication with the ground segment. One of the main problems encountered is significant Doppler frequency shifts, which can disrupt signal transmission and require precise adjustments to maintain stable communications. This paper presents a software solution to effectively compensate for the Doppler shift, along with a hardware implementation to manage the two available polarizations at the station: right-hand circular polarization (RHCP) and left-hand circular polarization (LHCP). This polarization management is necessary because the demodulator used in our case possesses only a single input. This solution has been implemented in an existing S-band ground station (GS) located in Oran, Algeria. The experimental results obtained during actual passes of the ALSAT-2A and ALSAT-2B satellites, whose orbits are 180 degrees apart, were satisfactory. The implemented solution showed good results, with accuracy comparable to the estimated Doppler frequency, without any loss of telemetry at the ground segment level.
Keywords: Alsat-2A Satellite; Alsat-2B Satellite; CDM 600 Application; Doppler shift; Estimated Doppler shift